Clinical Experience and Results of Microsurgical Resection of Arterioveonous Malformation in the Presence of Space-Occupying Intracerebral Hematoma. Issue 1 (15th March 2017) - Barone, Damiano G.; Marcus, Hani J.; Guilfoyle, Mathew R.; Higgins, J. Nicholas P.; Antoun, Nagui; Santarius, Thomas; Trivedi, Rikin A.; Kirollos, Ramez W.
Abstract: BACKGROUND: Management of ruptured arteriovenous malformations (AVMs) with a mass-producing intracerebral hematoma (ICH) represents a surgical dilemma. OBJECTIVE: To evaluate the clinical outcome and obliteration rates of microsurgical resection of AVM when performed concomitantly with evacuation of an associated space-occupying ICH. METHODS: Data of patients with AVM were collected prospectively. Cases were identified in which an AVM was resected and an associated space-occupying ICH was evacuated at the same time, and divided into "group 1, " in which the surgery was performed acutely within 48 h of presentation (secondary to elevated intracranial pressure); and "group 2, " in which selected patients were operated upon in the presence of a liquefying ICH in the "subacute" stage. Clinical outcomes were assessed using the modified Rankin Scale, with a score of 0 to 2 considered a good outcome. Obliteration rates were assessed using postoperative angiography. RESULTS: From 2001 to 2015, 131 patients underwent microsurgical resection of an AVM, of which 65 cases were included. In "group 1" (n = 21; Spetzler-Ponce class A = 13, class B = 5, and class C = 3), 11 of 21 (52%) had a good outcome and in 18 of 19 (95%) of those who had a postoperative angiogram the AVMs were completely obliterated. In "group 2" (n = 44; Spetzler-Ponce class A = 33, class B = 9, and class C = 2), 31 of 44 (93%) had a good outcome and 42 of 44 (95%) were obliterated with a single procedure. For supratentorial AVMs, the ICH cavity was utilized to provide an operative trajectory to a deep AVM in 11 cases, and in 26 cases the ICH cavity was deep to the AVM and hence facilitated the deep dissection of the nidus. CONCLUSION: In selected patients the presence of a liquefying ICH cavity may facilitate the resection of AVMs when performed in the subacute stage resulting in a good neurological outcome and high obliteration rate.